Theoretical perspectives on the new era of central banking. Issue 4 (December 2018) - Fontan, Clément; Carré, Emmanuel; L'Oeillet, Guillaume
Abstract The role played by central banks in our economies has changed drastically since 2007, when they became key players in the stabilisation of financial and economic systems. In addition to gaining new competences, their policies strayed increasingly into the political realm and became more controversial. This new era of central banking has revived scholarly debates and vibrant future research perspectives on both dimensions of their independence: towards political and financial institutions. In this article, we review the theoretical debates between economists, political scientists, economic sociologists, and political philosophers on this issue.